Legal Certification Requirements to Teach and Supervise Art in the Public Schools of the Fifty (50) States and the District of Columbia. Final Report - Heilman, Horace F.; Kutztown State Coll., PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
The basic objective of the study was centered on the legal minimum certification requirements to teach art in the public schools. A survey form submitted to the certification officers of the 50 States and the District of Columbia provided the desired information. Accumulated data is intended to reveal the present status of certification requirements and educational preparation. Evaluation of the surveys submitted by the responding certification officers indicated a greater emphasis on United States citizenship and a slightly greater non-requirement of a loyalty oath. The title of the certificate issued to the neophyte art teacher is definitely dissimilar for almost every state certification department. Educational requirements are well established for general and professional education. Analysis of the responses to the survey indicate a need to re-evaluate the specialization requirements for certification to teach art. There is a need for a modicum of certification agreement to facilitate reciprocal certification of art teachers among the several states. (Author/CK)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
Contract Number: OEG-6-10-036.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Art Teachers; Beginning Teachers; Public Schools; State Legislation; Surveys; Teacher Certification